Synthesis and characterization of high-molar-mass star-shaped poly(l-lactide)s - Michalski, A.; Łapienis, G. (Polimery, 2021)
The synthesis of high-molar-mass linear and 6-arm star-shaped poly(l-lactide)s(PLLA’s) is presented. Dipentaerythritol and benzyl alcohol were used asinitiators and Sn(Oct)2 was applied asa catalyst in the ring-opening polymerization (ROP) of l-lactide (l-LA) carried out at 130 °C. The prepared PLLA’s were characterized by SEC (size exclusion chromatography), 1H NMR (proton nuclear magnetic resonance spectroscopy), DSC (differential scanning calorimetry), and TGA (thermogravimetric analysis). The structure of the obtained star-shaped polymers was confirmed by comparison of the radii of gyration (Rg) determined by SEC for the linear and star macromolecules. The thermal properties of PLLA’s were shown for the wide range of molar masses. Additionally, it was confirmed that Irganox stabilizer has an influence on the thermal stability of PLLA’s.